Minimum Wages and Training Revisited - Neumark, David; Wascher, William (Journal of Labor Economics, 2001)
Theory predicts that minimum wages will reduce employer‐provided on‐the‐job training designed to improve workers' skills on the current job, but it is ambiguous regarding training that workers obtain to qualify for a job. We estimate the effects of minimum wages on both types of training received by young workers, exploiting cross‐state variation in minimum wage increases. Much of the evidence supports the hypothesis that higher minimum wages reduce formal training to improve skills on the current job. But there is little or no evidence of offsetting increases in training undertaken to qualify for or obtain jobs.